The relationships among food neophobia, mediterranean diet adherence, and eating disorder risk among university students: a cross-sectional study - Nilufer Ozkan; Fatma Hazan Gul (Journal of Health, Population and Nutrition)
Abstract Background Food neophobia, characterized by the fear of unfamiliar foods, can be influenced by environmental, cultural, and genetic factors, leading to decreased consumption of novel or diverse foods. Understanding the impact of Mediterranean diet adherence and eating disorders on dietary behaviors is crucial, particularly for young adults who are developing lifelong eating patterns. Methods The aim of this study was to investigate the relationships among food neophobia, Mediterranean diet adherence, and eating disorders in university students aged 18–24 years. A cross-sectional study was conducted with 1277 students (67.2% female) via an online questionnaire to assess sociodemographic characteristics, food neophobia (Food Neophobia Scale, FNS), Mediterranean diet adherence (KIDMED), and eating disorder risk (Eating Disorder Examination Questionnaire, EDE-Q). Results Most participants (67.7%) had a normal body mass index (BMI), 19.3% were classified as overweight, and 3.7% were classified as obese. Compared with male students, female students had significantly higher FNS scores (40.8 ± 9.21) (38.5 ± 10.97, p < 0.05), indicating greater food neophobia among women. Similarly, men’s EDE-Q scores (3.5 ± 3.32) were significantly lower than those of women (4.4 ± 4.05, p < 0.05). Most participants (69.5%) did not experience food neophobia, and underweight individuals (11.0%) were more neophobic than obese individuals (4.4%). No significant differences were observed according to BMI (p > 0.05). A positive correlation was found between age and KIDMED adherence, whereas a negative correlation was observed between BMI and EDE-Q scores regarding food neophobia. The effects of BMI on food neophobia and the risk of eating disorders were found to vary by sex. Conclusions These findings suggest that food neophobia may harm Mediterranean diet adherence and increase the risk of eating disorders among university students. Targeted interventions addressing food neophobia could promote healthier eating habits, such as the Mediterranean diet, thereby reducing disordered eating behaviors and associated risks. Further research is needed to confirm these findings, improve population nutritional habits and mental health outcomes, and develop effective public health strategies. Graphical Abstract